An Analysis of Sharia and Conventional Shares’ System at Indonesia Stock Exchange - Hersugondo Hersugondo; Cholimatul Sadiyah; Eka Handriani; Herry Subagyo; Sih Darmi Astuti (Universitas Muhammadiyah Sidoarjo, 2020)
There are lots of alternative investing. It is started from investment real assets, securities, from conventional and manifold sharia. Islamic Capital market and conventional have some type securities which have different risk level of risks. A stock is one of securities among other securities that have the high level of risk. One of the risks that exists in the stock is fluctuations price, it is commonly called as volatility. The aim of this research is to identifiy the risk of sharia stock and conventional stock in Indonesia Stock Exchange (BEI) by using Jakarta Islamic Indekx (JII) and LQ45 Indeks variabels. In our research, we use time series started on 1 January 2015 to 10 October 2016 from yahoo finance with ARCH/GARCH and EGARCH models processed by Eview 8. Based on research finding with GARCH and EGARCH, this research tends to EGARCH. The fist finding shows that volatility stock JII lower, 0,075 than LQ45 0,0316. If volatility is higher, it means the stability degree lower. Both of those stocks are dominated by bad news and good news. Between JII and LQ45, the news respon is higher on LQ45. It means the volatility risk impact higher on LQ45. The third finding is the JII forecasting results through EGARCH has refrection proportion JII has smaller 0,194 than LQ45 0,678. It means that JII volatility is lower than LQ45.